Direct and Indirect Effects of Cytomegalovirus-Induced γδ T Cells after Kidney Transplantation - Couzi, Lionel; Pitard, Vincent; Moreau, Jean-François; Merville, Pierre; Déchanet-Merville, Julie (Frontiers in Immunology, 2015)
Despite effective anti-viral therapies, cytomegalovirus (CMV) is still associated with direct (CMV disease) and indirect effects (rejection and poor graft survival) in kidney transplant recipients. Recently, an unconventional T cell population (collectively designated as Vδ2neg γδ T cells) has been characterized during the anti-CMV immune response in all solid-organ and bone-marrow transplant recipients, neonates, and healthy people. These CMV-induced γδ T cells undergo a dramatic and stable expansion after CMV infection, in a conventional ‘adaptive’ manner. Similarly as CMV-specific CD8+ αβ T cells, they exhibit an effector/memory TEMRA phenotype and cytotoxic effector functions. Activation of Vd2neg gd T cells by CMV-infected cells involves the TCR and still ill-defined co-stimulatory molecules such LFA-1. A multiple of Vd2neg gd TCR ligands are apparently recognized on CMV-infected cells, the first one identified being the MHC-related molecule endothelial protein C receptor (EPCR). A singularity of CMV-induced Vd2neg gd T cells is to acquire CD16 expression and to exert an antibody-dependent cell-mediated inhibition on CMV replication, which is controlled by a specific cytokine microenvironment. Beyond the well-demonstrated direct anti-CMV effect of Vδ2neg γδ T cells, unexpected indirect effects of these cells have been also observed in the context of kidney transplantation. CMV-induced Vδ2neg γδ T cells have been involved in surveillance of malignancy subsequent to long term immunosuppression. Moreover, CMV-induced CD16+ γδ T cells are cell effectors of antibody-mediated rejection of kidney transplants, and represent a new physiopathological contribution to the well-known association between CMV infection and poor graft survival. All these basic and clinical studies paved the road to the development of a future γδ T cell-based immunotherapy. In the meantime, γδ T cell monitoring should prove a valuable immunological biomarker in the management of CMV infection.